Asian monsoon rainfall variation during the Pliocene forced by global temperature change - Hanlin Wang (Nature Portfolio, 2019)
Asian summer monsoons and their links to global temperature changes have been the subject of intense debate. Here the authors reconstruct the Asian monsoon climate since the late Miocene, using plant silica records of C4 and C3 grasses in central China, and find that global cooling caused Asian monsoon rainfall to decrease markedly in the late Pliocene.